Productivity and Technical Efficiency of Poultry Egg Production in Nigeria - Ojo, S.O. (International Journal of Poultry Science, 2003)
The study examined the Productivity and Technical Efficiency of Poultry egg production in Nigeria using the stochastic frontier production function analysis. Primary data were collected using a set of structured questionnaire from two hundred poultry egg farmers who were selected using multi stage sampling techniques, from five Local Government Areas (LGA) of Osun state, Nigeria. Results showed that poultry egg production was in the rational stage of production (stage II) as depicted by the Returns to Scale (RTS) of 0.771. The variables of interest, stock of birds, operating costs, and other costs were effectively allocated and used, as confirmed by each variable having estimated coefficient value between zero and unity. The Technical Efficiencies of the farmers varied widely between 0.239 and 0.933 with a mean of 0.763 and about seventy nine percent of the farmers had T.E. exceeding 0.70. This study further observed that only location of farm (nearness to urban centre) positively affected T.E while increase in the other socio-economic variables, age, experience and education led to decrease in T.E.